2001
DOI: 10.1016/s0921-4534(01)00782-1
|View full text |Cite
|
Sign up to set email alerts
|

Flux jumping and a bulk-to-granular transition in the magnetization of a compacted and sintered MgB2 superconductor

Abstract: In this letter, we report the results of field (H) and temperature (T) dependent magnetization (M) measurements of a pellet of uniform, large-grain sintered MgB 2 . We show that at low temperatures the size of the pellet and its critical current density, J c (H) --i.e. its M(H) --ensure low field flux jumping, which of course ceases when M(H) drops below a critical value. With further increase of H and T the individual grains decouple and the M(H) loops drop to lower lying branches, unresolved in the usual ful… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 12 publications
3
57
0
Order By: Relevance
“…Dou et al 21 reported evidence for decoupling of the grains in sintered MgB 2 , both through partial flux jumping and a step in the field dependence of Jc. These authors showed that initial bulk superconductor samples break down into a granular assembly beyond a certain critical value of field and temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Dou et al 21 reported evidence for decoupling of the grains in sintered MgB 2 , both through partial flux jumping and a step in the field dependence of Jc. These authors showed that initial bulk superconductor samples break down into a granular assembly beyond a certain critical value of field and temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The density of both samples is about 1.6g/cm 3 . reported for a MgB 2 pellet with grain sizes as large as 200 µm [18]. In addition, the magnetisation hysteresis is much larger than for a weak-linked MgB 2 sample which was sintered at 800 o C using high pressure and reacted MgB 2 powders used as starting material [19].…”
Section: Resultsmentioning
confidence: 99%
“…This may be why the MgB 2 does not show that ''weak-link'' effect characteristic of the high-T c superconductors. In fact, the large grains of 200 m in the sample sintered at 800°C for 4 h following furnace cooling decouple at high field, 19 while the nanodomain boundaries in the samples sintered at 745°C-840°C for 5-30 min subsequently air quenched present no barrier to the current. 14 This shows that the nanodomain boundaries are transparent to the percolated current.…”
mentioning
confidence: 98%